Analysis of the Implementation of Partnership Relationship Between Gojek Companies and Drivers - Siti Hawa Hasibuan (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2024)
GO-JEK is an innovative company in the land transportation sector in Indonesia. They offer a variety of services such as travel, food delivery, house cleaning, massage services, and online shopping, all of which can be accessed through the Android mobile platform. As a technology company with a social mission, GO-JEK aims to improve the welfare of workers in various informal sectors. Their operations are based on three core values: speed, innovation, and social impact. GO-JEK provides two categories of services: Go-Jek, which focuses on transportation, and Go-Life, which includes services outside of transportation. The relationship between GO-JEK and driver-partners is not in the form of an employer-employee relationship, but a partnership agreement. GO-JEK defines itself as a social enterprise that is leading the motorcycle taxi transportation revolution, as stated on their official website. The concept of agreements is an integral part of their work system. In this series, the author is interested in conducting research to explore how PT. Gojek builds effective relationships with drivers based on partnership agreements. This study aims to investigate the strategies used by PT. Gojek to build a strong relationship with drivers within the framework of this partnership agreement. The author uses normative legal research methods, especially literature law research, as the chosen approach. The main data for this study mainly consists of literature materials, which are considered secondary data in the field of research. The data collection technique used is a thorough review of relevant literature. This study uses qualitative analysis, which is a method that provides descriptive insights in the form of writing.